Effectiveness of the stad reading aloud model to improve narrative text literacy - Muslikhin Muslikhin; Tri Joko Raharjo; Panca Dewi Purwati; Galih Cahya Pratama (Jurnal Ilmiah Pendidikan Dasar)
This study was conducted to provide an overview and description of improving narrative text literacy by using the reading aloud method as one way to improve and strengthen students' narrative text literacy skills in the AKM class. The approach taken in this writing is to use a quantitative approach, namely by obtaining pre-test and post-test data processed using SPSS data, namely the Paired Sample T-Test. The results of this study indicate that a reading culture by reading aloud can have an influence on improving students' narrative text literacy at Ketanggungan 07 Brebes Elementary School. Students' enthusiasm in understanding narrative texts with this method is quite good. This is evidenced by an increase in the AKM class from data processing, the data obtained is p <0.05, H0 is rejected which indicates that there is a significant increase.